2004
DOI: 10.1515/bc.2004.146
|View full text |Cite
|
Sign up to set email alerts
|

Structural flexibility of small GTPases. Can it explain their functional versatility?

Abstract: Multiple interactions with many different partners are responsible for the amazing functional versatility of proteins, especially those participating in cellular regulation. The structural properties that could facilitate multiple interactions are examined for small GTPases. The role of cellular constraints, compartmentation and scaffolds on protein-protein interactions is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 170 publications
0
5
0
Order By: Relevance
“…One way, but not the only way, to transmit signals from these receptors after activation is through G proteins. For more information, see [ 19 , 78 - 80 ] and the recent excellent review by Ilka Böhme and Annette G. Beck-Sickinger in this journal [ 81 ].…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way, but not the only way, to transmit signals from these receptors after activation is through G proteins. For more information, see [ 19 , 78 - 80 ] and the recent excellent review by Ilka Böhme and Annette G. Beck-Sickinger in this journal [ 81 ].…”
Section: Commentsmentioning
confidence: 99%
“…A focal point of my discussion of the route from gene to protein is the plasticity of structure and function of some proteins, notably of antibodies and receptors [ 19 ] which allows one and the same protein to assume different structures and functions in the same cellular environment. I shall give examples of pliable and adaptable proteins and shall cite possible causes of ligand-induced malleability of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…24 Thus, the low GTPase activity of some calexcitins in vitro may simply reflect on the lack of Structure of the Neuronal Protein Calexcitin an activator protein. Instead, it may be that calexcitin is actually an activator of a partner GTPase and acts in much the same way as calmodulin, which is known to regulate GTPases by binding to the GTPase activator protein GAP.…”
Section: Implications For the Physiological Role Of Calexcitinmentioning
confidence: 99%
“…Ras and structurally related proteins form the small GTPase family, a superfamily of monomeric GTP binding proteins (G-protein), which exists in various organisms [5], [6]. Numbers of studies of small GTPase have been reported in relation to their characteristics and distribution to variety of organisms [structures [7][9], functions [10], [11] and oncogenesis [12][15] of mammals [16][18], plants [19] and fungi [20][24]]. Commonly, the small GTPase plays central roles in signal transduction across membranes via the interaction with GDP/GTP exchange factors (GEF), GTPase activation proteins (GAP) and other regulators [10], [25][27].…”
Section: Introductionmentioning
confidence: 99%